PENGARUH MODEL PENCAPAIAN KONSEP PADA MATERI LOGIKA DASAR TERHADAP HASIL BELAJAR MAHASISWA DI STKIP MUHAMMADIYAH PAGARALAM - Hariani Juwita; Neni Lismareni (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The purpose of this research is to find out the effect of the concept achievement model on basic logic material on student learning outcomes, because this basic logic material is a course in STKIP Muhammadiyah Pagaralam. Model Achievement The concept taken is one of the learning models that invites students to understand the concepts of mathematics learning. The population and sample in this study were STKIP Muhammadiyah Pagaralam students majoring in Semester 1 Mathematics Education. The research method used in this study was the experimental method with the True Experimental Design model in the "posttes-only control design" category. Data collection techniques in the form of documentation and tests. After the data collection is finished, the data is analyzed by data analysis techniques that can be broken down into documentation analysis techniques and test analysis techniques, where for the test analysis technique a statistical formula is used, namely simple liner regression followed by the SPSS test (Statistical Product and Service Solution). The results of this study can be seen the value of R = 0.456 where R is a symbol of the Correlation Coefficient, this value indicates that the relationship between the two research variables is in the sufficient category. And on the Determinant coefficient of R Square (r2) of 0.208, the value means that the influence of the concept achievement model (X) on student learning outcomes (Y) is 20.8% and the rest is influenced by other variables as much as 79.2% influenced by other factors outside the variable X